Artificial Intelligence untuk pendidikan keguruan perspektif mahasiswa internasional dan implikasi untuk Pendidikan Islam - Muthohar, Sofa; Filasofa, Lilif Muallifatul Khorida; Azzahra, Hilyatul Karimah; Nasikhin; Nabila, Annisa Fara (TA`DIBUNA, 2025)
This research explores the opportunities and challenges of developing artificial intelligence (AI) for teacher education programs from the perspective of international students in Indonesia, the Philippines, and Japan. This study uses a narrative inquiry approach through in-depth interviews with 15 students. The results reveal differing dynamics in AI implementation across these three archipelagic countries. In Indonesia, information technology and the drive to improve educational quality motivate AI adoption, although infrastructure limitations pose a barrier. Filipino students support AI adoption due to the importance of technology in education, but financial and training aspects remain obstacles. Meanwhile, Japanese students are driven by technological advancement and an innovative culture but express concerns about human workforce replacement and the ethical aspects of AI. These findings highlight the need for effective policies tailored to each country's unique characteristics to optimize AI in teacher trainings AbstrakPenelitian ini mengeksplorasi peluang dan tantangan pengembangan teknologi informasi berbantantun kecerdasan buatan (AI) untuk program pendidikan guru dari perspektif mahasiswa internasional di Indonesia, Filipina, dan Jepang. Studi ini menggunakan pendekatan naratif inkuiri melalui wawancara mendalam dengan 15 mahasiswa. Hasilnya menunjukkan dinamika yang berbeda dalam penerapan AI di tiga negara kepulauan ini. Di Indonesia, teknologi informasi dan peningkatan kualitas pendidikan memotivasi penerapan AI, meskipun keterbatasan infrastruktur menjadi hambatan. Mahasiswa Filipina mendukung adopsi AI karena pentingnya teknologi dalam pendidikan, namun terkendala aspek finansial dan pelatihan. Sementara itu, mahasiswa Jepang terdorong oleh kemajuan teknologi dan budaya inovatif, tetapi khawatir tentang penggantian tenaga manusia dan aspek etika AI. Temuan ini menggarisbawahi pentingnya kebijakan efektif yang disesuaikan dengan karakteristik masing-masing negara dalam mengoptimalkan AI untuk pendidikan keguruan.